Reciprocal Interaction of 24-Hour Blood Pressure Variability and Systolic Blood Pressure on Outcome in Stroke Thrombolysis. Issue 7 (July 2017) - Kellert, Lars; Hametner, Christian; Ahmed, Niaz; Rauch, Geraldine; MacLeod, Mary J.; Perini, Francesco; Lees, Kennedy R.; Ringleb, Peter A.
Abstract : Background and Purpose—: Significance and management of blood pressure (BP) changes in acute stroke care are unclear. Here, we aimed to investigate the impact of 24-hour BP variability (BPV) on outcome in patients with acute ischemic stroke treated with intravenous thrombolysis. Methods—: From the Safe Implementation of Treatment in Stroke International Stroke Thrombolysis registry, 28 976 patients with documented pre-treatment systolic BP at 2 and 24 hours were analyzed. The primary measure of BP variability was successive variability. Data were preprocessed using coarsened exact matching. We assessed early neurological improvement, symptomatic intracerebral hemorrhage (SICH), and long-term functional outcome (modified Rankin Scale [mRS] at 90 days) by binary and ordinal regression analyses. Results—: Attempts to explain successive variation for analysis of BPV with patients characteristics at admission found systolic BP (5.5% variance) to be most influential, yet 92% of BPV variance remained unexplained. Independently from systolic BP, successive variation for analysis of BPV was associated with poor functional outcome mRS score of 0 to 2 (odds ratio [OR], 0.94; 95% confidence interval [CI], 0.90–0.98), disadvantage across the shift of mRS (OR, 1.04; 95% CI, 1.01–1.08), mortality (OR, 1.10; 95% CI, 1.01–1.08), SICHSITS (OR, 1.14; 95% CI, 1.06–1.23), and SICHECASS (OR, 1.24; 95% CI, 1.10–1.40; ECASS [European Cooperative Acute Stroke Study 2]). Analyzing successive variation for analysis of BPV as a function of pre-treatment, systolic BP significantly improved the prediction of functional outcome (mRS score of 0–1, mRS score of 0–2, neurological improvement, mRS-shift: all P interaction <0.01). Excluding patients with atrial fibrillation in a sensitivity analysis gave consistent results overall. Conclusions—: This study suggests the need for a more individual BP management accounting for pre-treatment BP and the acute BP course (ie, BPV) to achieve best possible outcome for the patient. Abstract : Supplemental Digital Content is available in the text.